Sin in the New Testament - Siker, Jeffrey S. (Essentials of bibliocal studies, 2020)
Whatever happened to sin? --A taxonomy of sin in the New Testament worlds --Sin in the Gospel of Mark --Sin in the Gospel of Matthew --Sin in Luke-Acts --Sin in the Gospel of John and the Johannine Epistles --Sin in the letters of Paul and Deutero-Paul --Sin in Hebrews, James, and 1 and 2 Peter --Sin in Jude, Revelation, and beyond --Sin then and now.